THE ROLE OF THE MARDUK GOD IN THE INCANTATIONS TEXTS AND EXORCISM IN MESOPOTAMIA - Qasim, Luqman (Humanities Journal of University of Zakho, 2025)
The Marduk god is one of the most important main gods in ancient Iraq. His name was mentioned in many Sumerian writings in different forms, and emerged around (2600 BC). Also, he is the protector god of the Babylon city and was given the position of gods king in the Babylon city. The Marduk god played a great role in the Spells texts, as man has imagined himself since ancient times surrounded by all kinds of evil forces that hit him, as a result of committing sins and wrongdoings. Hence, the Mesopotamia inhabitants in their various historical eras believed that the consequences of human illnesses likewise epidemics were the result of the gods’ irritation at humans, owing to their committing sins also crimes, and holding humans accountable for the sins and disobediences they commit, and thus evil spirits in addition demons that cause diseases and harm are imposed on them. This is what prompted people to seek the assistance of priests in order to get rid of these diseases and evil spirits through some rituals and religious practices, including spells with the assistance of the concerned gods. The most prominent of these gods specialized in expelling demons and spirits is the Marduk god. The importance of this research comes to show the major role of the Marduk god in spells. In many magical forms, the magician would seek support from the Marduk god in spells to free the sickening person from the grip of evil demons. In addition to his role in healing patients, the role of the Marduk god in fighting evil is evident from the above, as he is the spirit of magic and spells that expels evil represented by jinn and evil spirits from the body of the sickening person. Whereas, others were used to nullify the works of magic and the hazards of demons that triggered harm and diseases to people, including the plague and headaches. Also, this study attempts to explore the most significant diseases that were treated by spells in Mesopotamia, and some of these spells were specific to winds and purification.